2018 Annual Report of the European Liver Transplant Registry (ELTR) – 50‐year evolution of liver transplantation. (5th November 2018) - Adam, René; Karam, Vincent; Cailliez, Valérie; O Grady, John G.; Mirza, Darius; Cherqui, Daniel; Klempnauer, Jurgen; Salizzoni, Mauro; Pratschke, Johann; Jamieson, Neville; Hidalgo, Ernest; Paul, Andreas; et al.
Summary: The purpose of this registry study was to provide an overview of trends and results of liver transplantation (LT) in Europe from 1968 to 2016. These data on LT were collected prospectively from 169 centers from 32 countries, in the European Liver Transplant Registry (ELTR) beginning in 1968. This overview provides epidemiological data, as well as information on evolution of techniques, and outcomes in LT in Europe over more than five decades; something that cannot be obtained from only a single center experience.